2008
DOI: 10.1038/nm1736
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and pharmacologic inhibition of mitochondrial-dependent necrosis attenuates muscular dystrophy

Abstract: Muscular dystrophies comprise a diverse group of genetic disorders that lead to muscle wasting and, in many instances, premature death 1 . Many mutations that cause muscular dystrophy compromise the support network that connects myofilament proteins within the cell to the basal lamina outside the cell, rendering the sarcolemma more permeable or leaky. Here we show that deletion of the gene encoding cyclophilin D (Ppif) rendered mitochondria largely insensitive to the calcium overloadinduced swelling associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
314
2
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 332 publications
(332 citation statements)
references
References 30 publications
9
314
2
7
Order By: Relevance
“…Deux articles, parus simultanément en mars 2008, illustrent ce type de démarche en proposant de traiter certaines dystrophies musculaires par une thérapeutique ciblée sur la mitochondrie [2,3].…”
Section: « It Is Suggested That the Mechanism Of Muscle-cell Necrosisunclassified
See 1 more Smart Citation
“…Deux articles, parus simultanément en mars 2008, illustrent ce type de démarche en proposant de traiter certaines dystrophies musculaires par une thérapeutique ciblée sur la mitochondrie [2,3].…”
Section: « It Is Suggested That the Mechanism Of Muscle-cell Necrosisunclassified
“…En substituant sur la molécule de CsA le résidu sarcosine en position 3 par une N-méthyle-D-ala, et le résidu N-méthyle-leucine en position 4 par un reste N-éthyle-val, les chimistes de la firme DebioPharm de Lausanne (Suisse) sont justement parvenus à obtenir un analogue (Debio-025) qui ne cible plus que CypD, ce qui en fait un médi-cament purement mitochondrial, dépourvu de tout effet immunosuppresseur [19]. Pour démontrer que CypD est une cible thérapeutique intéressante dans certaines DM, Millay et al [2] ont dans un premier temps croisé des souris Scgd -/-ou des souris Lama2 -/-(voir Tableau I) avec des souris dont le gène de CypD a été invalidé par KO de topographie subcellulaire très variées. Schématiquement, on distingue les DM se manifestant après la naissance (une trentaine de phénotypes cliniques différents, et 20 gènes identifiés), et les DM congé-nitales (une vingtaine de phénotypes, 12 gènes identifiés).…”
Section: Les Dystrophies Musculairesunclassified
“…2 The final category involves modifying the disease process downstream of the dystrophin deficiency and a number of disease-modifying agents such as angiotensin II type 1 receptor blockade (Losartan), a blockade of TNF-a and coenzyme Q10 have been tested and shown to be effective in the mouse model of DMD. 5,6 The results presented by Millay et al 1 are an important addition to this latter category and present a novel treatment target.…”
mentioning
confidence: 93%
“…7 Millay et al demonstrate that crossing these Ppif À/À mice with mice lacking d sarcoglycan (Scgd À/À , a mouse model of limb girdle muscular dystrophy 2F) or laminin a2 (Lama2 À/À , a mouse model of congenital muscular dystrophy 1A), markedly attenuated the disease process, although it did not prevent it entirely. 1 They also showed that two times daily treatment for 6 weeks with Debio-025, a cyclophilin inhibitor, substantially reduced the disease in mdx and Scgd À/À mice.…”
mentioning
confidence: 98%
See 1 more Smart Citation